The secret of Roan Inish [videorecording (DVD)] - Sayles, John, 1950-; Green, Sarah, 1957-; Renzi, Maggie; Lally, Mick; Colgan, Eileen; Lynch, John, 1961-; Courtney, Jeni; Fry, Rosalie K. (Columbia Tristar Home Video, 2000)
A magical tale of a girl whose search for her missing brother brings an Irish legend to life.